Analysis of Key Factors for The Success of Waqf Through Moneyin The Dhuafa's Wallet Waspada - Alya Rahma Siregar; Juliana Nasution; Nurul Jannah (Jurnal Manajemen Bisnis, 2024)
The aim of this research is to analyze, explore and explain the key factors for the success of waqf through money in the wallets of the dhuafa alert. This research intends to study the key factors of waqf through money and how successful waqf through money is in Dompet Dhuafa Waspada. Qualitative research is a method used by collecting data through observation, interviews and documentation. The results of this research found that the key factor in the success of waqf through money in Dompet Dhuafa Waspada is creating programs that are attractive to the community as an indicator of people who want to donate to Dompet Dhuafa Waspada. Be alert to interesting programs such as mosque construction waqf, ambulance car waqf, Al-Quran waqf and livestock fattening wells. This is what really influences its success from other factors. Waqf through cash must be preserved and is not allowed to be sold, inherited or gifted to immovable or movable property. Because waqf through money is carried out widely and is not limited. However, those who are entitled to receive cash waqf include those who cannot afford it and the poor.